study the causes of torrents and the extent of their damages in the city of Mandali - shuail Jarmat, Hussain (Journal of College of Education, 2021)
Torrents are considered as one of the most important natural disasters to which many regions of the world and the study area are subjected to in particular from time to time, although they fall within the belt of semi-arid regions globally, as the geological nature of the region is characterized by the abundance of interconnected valleys whose composition dates back to ancient times, as it extends The mountain baskets in it from the east and north-east, which made them good areas to collect rain water, and the occurrence of the phenomenon of torrential torrents, which resulted in a lot of material damage and the displacement of the villagers to the neighboring areas to escape the threat of damaging torrents. From this standpoint, the current research dealt with studying torrents and the extent of the damages resulting from them in the city of Mandali.